Korelasi Indeks Prestasi Kumulatif dan Masa Studi dengan Uji Kompetensi Perawat - Jarman Jarman; Takdir Tahir; Syahrul Syahrul; Rosyidah Arafat; Nurmaulid Nurmaulid (Jurnal Kesehatan Manarang, 2022)
Nursing competency test is a process that must be passed by nursing students to measure the suitability between knowledge, skills and student behavior against competency standards of graduates who meet work competency standards. Only students who pass the competency test are able to enter health services. Passing competency test is certainly influenced by various aspects, some of them are GPA and study period. Both of these things are an important role in the teaching and learning process that a student goes through. GPA is an indicator to assess learning achievement and the length of study is the time taken by the student to complete his studies. However, recently there has been an assumption among students that a high GPA does not guarantee in passing competency test and a prolonged study period does not prevent students from first passing the competency test, therefore researchers are interested in seeing the correlation of the two things. Objective The aim of the reasearch was to determine the correlation between Grade Point Average (GPA) and the period of study toward passing the Nursing Competency Test in Nursing Departement of the Health Polytechnic of the Ministry of Health in Mamuju. Method This research is an analytic study with cross sectional design using secondary data. This research used total sampling with a sample size of 138. The Result showed that GPA had p<0,001 with correlation r= 0,908 and the study period had p<0,001 with correlation r=0,291. The Conclusion of the research is GPA had positive corelation very strong and the study period also had positive corelation but poor corelation.